Solvent-induced viscosity changes in ionic liquids - a review - Khupse, Nageshwar D.; Kumar, Anil (Proceedings of the National Academy of Sciences India Section A-Physical Sciences, 2010)
The high viscosity of several ionic liquids is an undesirable property for their applications in a variety of chemical reactions and electrochemical devices. Addition of a solvent in an ionic liquid is known to reduce its high viscosity to a great extent. In this review, an attempt has been made to examine the published data on the reduction in viscosities of many ionic liquids upon the addition of molecular solvents, including water. A tentative description has been provided for the drop in viscosities under these conditions. Analysis of the viscosity data with the help of empirical equations has been summarized. This critical review also outlines the future outlook of the required studies that might be useful to those who are interested in using ionic liquids for a variety of applications.
Keywords: ionic liquids; solvent; viscosity

Solvent-mediated molar conductivity of protic ionic liquids - Thawarkar, Sachin; Khupse, Nageshwar D.; Kumar, Anil (Physical Chemistry Chemical Physics, 2015)
The molar conductivity, A(m), of protic ionic liquids (PILs) in molecular solvents is measured at 298.15 K. The decrease in the A(m) values of PILs is observed with an increase in the concentration of PILs. The limiting molar conductivities, A(m)(0), were obtained for each PIL in different molecular solvents using a least squares method. The A(m)(0) data for PILs were correlated with the structural aspects of PILs and solvent properties. The polar protic solvents show poor ionic association as compared to the polar aprotic solvents, which is discussed on the basis of the hydrogen bond donating (HBD) ability of solvents and PILs. The alkyl chain substitution of anions plays a significant role in the ionic association of the PILs. The diffusion coefficient D-0 and the transport number t were determined, which were consistent with the A(m)(0) values of PILs in water. The A(m)(0) and D-0 values are dependent on the hydrodynamic radius of anions of these ionic liquids. The extent of ionic association for each PIL was discussed using temperature dependent A(m) data for aqueous PIL systems in terms of the Walden plot.